PENENTUAN PRIORITAS KESEJAHTERAAN KELUARGA MENGGUNAKAN METODE THE EXTENDED PROMETHEE II - Wati, Masna; Lubis, Ferry Miechel; Tejawati, Andi (ILKOM Jurnal Ilmiah, 2020)
Indonesia is a developing country in which poverty is one of the problems faced by each province. The government continues to strive to overcome this problem of poverty to be able to create conditions for a prosperous society. The government's efforts to poverty alleviation are by providing some assistance programs. Therefore, it is necessary to build a decision support system that is useful to help the government to make a decision. This decision support system applies the EXPROM II (The Extended Promethee II) method with the weight of objective criteria. There are 15 criteria used based on SUSENAS data from the Statistics Indonesia of East Kalimantan Province. This research resulted in a decision support system that can give priority order of the level of family welfare so that it can be considered or referred by the local government or related agencies in distributing assistance to the society.